(3YeOI GdMSGHs - (3YR GdOjf EHQGgje Hf YHO GdhgGH Hf Ydj GdTGaYj, CHh GdeYGdj , GdYRjs
(3ChdgG (B:s
(3GdMeO ddg GdeOHQ GdMGOKGJ hHYO adeG QCjJ Cf Yde GdMSGH CLd GdYdhe GdQjGVjI hCfaYgG dPhi GdCdHGH s
(3BNQgG (B:s
(3hgh NeSI hYTQhf afNQL NeSI hKdGKI CNeGS hCQHYI CNeGS hgh GdeGd GdeWdhH hdfNJe GdcdGe ai gPG GdehVY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3Jdjg eSGFds
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdQjGVjGJs